Discursos de crianças do ensino fundamental sobre práticas escolares de avaliação - SILVA, Elenize Saraiva da (2021)
This paper analyzes discourses of elementary school students about assessment of learning, trying to understand the meanings that they attribute to the evaluation performed in the school context and how this practice can be thought as a device of discipline and control over minds and students' bodies from a varied number of institutional rituals. The analyzes are based on the thought of the French philosopher Michel Foucault, especially regarding the discussion about the relationship between discourse, knowledge and power and about the disciplinary power devices put into action by the school through evaluative practices. The study operates with the Foucaultian framework in dialogue with Brazilian authors from the field of educational assessment, such as Luckesi (2008); Hoffmann (1994, 1995, 2002); Esteban (2003); Saul (2010). The research is based on a qualitative approach, the empirical data were collected during the participation in the Institutional Program for Teaching Initiation Scholarships (PIBID) in a public school in Bragança-PA, where it was possible to hear the students of the 3rd class. and 5th grade of elementary school about their experiences with assessment, as well as characterizing the school's evaluation practices through dialogue with managers and teachers. The methodological procedures used were participant observation and semi-structured group interviews. Through participant observation, students experienced events related to the evaluation, as well as the teachers' practices in the classroom context. The semi-structured interview was conducted with a group of 10 children, 5 from each class, involving dynamics appropriate to their age group, in order to sensitize them to express themselves on the subject. The dialogue with the teaching teachers of both classes and with the management made it possible to complement data on the conception and practice of evaluation in the institution. The speeches of the students demonstrated that they have a strong perception of evaluation as a synonym of proof and examination, as well as attributing to this sense of fear, punishment and punishment, due to the disciplinary power that parents teachers exercise on children through assessment. The study argues that in the researched context the assessment involves attitudes and threatening behaviors by parents and teachers, which generates fear in students, fear of error, disapproval, failure. It is also evidenced that the evaluation practices at school are still based on a traditionalist model of education, overemphasizing the test as an instrument of control of the students, although often, in terms of proposal and arguments, school management and teachers defend progressive conceptions and the diversification of qualitative assessment procedures and instruments. In summary, it is suggested that research in the area of evaluation should further investigate what students internalize about evaluation processes, which can greatly contribute to the construction of another evaluative culture in the school, which improves performance monitoring practices. of the students in a more diagnostic and formative and less punitive sense.